Peran Kepemimpinan Kepala Daerah Dalam Penanggulangan Kemiskinan: Studi Kasus di Kabupaten B - Kartini, Mulyati (Jurnal Pendidikan Indonesia, 2025)
Poverty is still a complex problem in various regions, including Regency B, which requires an active role of local governments in creating effective solutions. The leadership of regional heads has an important influence in determining the direction of policies, strategies, and innovations that are able to reduce poverty rates. This study aims to analyze the leadership role of regional heads in poverty alleviation in Regency B and provide policy recommendations that are more targeted and sustainable. This study uses a qualitative method with a case study approach to understand the leadership role of regional heads in poverty alleviation. Data is collected through policy documentation, program reports, government documents, and relevant research. Data analysis is carried out with the Huberman & Miles model through data reduction, data presentation, and drawing valid and accountable conclusions. The results of the study show that the leadership of regional heads in Regency B plays an important role in reducing poverty rates through targeted and innovative policies. Local governments take advantage of local potential and collaborate with various parties to strengthen poverty alleviation programs.